Chiang Ching-kuo and the regional planning of Gannan under the influence of Soviet Experience (1941-1945): The planning practice of socialist ideological trend in modern China - Zhao, Li; Baihao, Li (International Planning History Society Proceedings, 2018)
In the early 1940s, regional planning theory and practice spread into China. Gannan Reform dominated by Chiang Ching-kuo was an important experiment and marked by socialist ideology from the Soviet-Russia. In Jiangxi Province, Chiang Ching-kuo formulated the regional development path of first social construction and post physical planning. As a proponent of Confucianism, he combined the Soviet-experience with traditional Confucian urban-rural governance rules of ancient China. Promoted by Chiang, the government formulated two five-year plans (1941-1949) in 1941 and 1943. Under planned economy system, government developed public and cooperative undertakings to construct various industries and built a model state as an example for China which attracted the attention of world. The plan was similar to the Five-Years Plan of Soviet and P.R. China, and had an obvious socialist character. Its annual plan and ten-systems were also similar to Chiang's Four-year Plan and Top Ten Construction in Taiwan in 1970s. Based on historical archives, research has focused on Chiang Ching-uo and Gannan Reform and explained that how the reform can combined the Sovietexperience, planned economy, Confucian experience with regional planning as the earliest regional planning in modern China in 1940s. It’s an extremely important issue that has not been excavated.